1992
DOI: 10.1042/bj2830261
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the expression of the mitochondrial 3-hydroxy-3-methylglutaryl-CoA synthase gene. Its role in the control of ketogenesis

Abstract: We have explored the role of mitochondrial 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) synthase in regulating ketogenesis. We had previously cloned the cDNA for mitochondrial HMG-CoA synthase and have now studied the regulation in vivo of the expression of this gene in rat liver. The amount of processed mitochondrial HMG-CoA synthase mRNA is rapidly changed in response to cyclic AMP, insulin, dexamethasone and refeeding, and is greatly increased by starvation, fat feeding and diabetes. We conclude that one point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 25 publications
5
70
1
Order By: Relevance
“…In order to study the hormonal regulation of the gene, our group previously carried out several in-vivo experiments to study the influence of dibutyryl CAMP, insulin, dexamethasone, a diet of fat, diabetes and refeeding after 24 h of fasting on mRNA levels. These results showed that the mRNA levels are strongly influenced by these effectors (Casals et al, 1992).…”
Section: The Promoter and 5' Flanking Regionmentioning
confidence: 51%
See 2 more Smart Citations
“…In order to study the hormonal regulation of the gene, our group previously carried out several in-vivo experiments to study the influence of dibutyryl CAMP, insulin, dexamethasone, a diet of fat, diabetes and refeeding after 24 h of fasting on mRNA levels. These results showed that the mRNA levels are strongly influenced by these effectors (Casals et al, 1992).…”
Section: The Promoter and 5' Flanking Regionmentioning
confidence: 51%
“…Transient transfection experiments confirm the presence of elements involved in the CAMP, insulin, dexamethasone and fatty-acid response in the proximal 1149 bp of the promoter region. These observations correlate with the regulation of the active enzyme by glucagon (Siess et al 1980), insulin (Quant et al, 1989) and with the in-vivo multihormonal regulation of the mRNA levels (Casals et al 1992). Further work is required in order to assign these regulatory elements to definite nucleotide sequences in the mitochondrial HMG-CoA promoter.…”
Section: The Promoter and 5' Flanking Regionmentioning
confidence: 68%
See 1 more Smart Citation
“…This suggests that as a consequence of relatively low glucocorticoid levels, hepatic glucocorticoid receptor activity was decreased in SR-BI-deficient mice. Furthermore, a significant decrease (243% to 265%) was observed in the hepatic mRNA expression of genes that are stimulated by the glucocorticoid receptor and are involved in hepatic lipid and glucose metabolism, such as cholesterol 7a-hydroxylase (CYP7A1) (20), HMG-CoA synthase (HMGCS) (21), and apolipoprotein A-IV (ApoA-IV) (22) (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that intramitochondrial 3-hydroxy-3-methylglutaryl-CoA (mHMG-CoA) synthase becomes an important locus of control under these conditions [71,72]. Insulin treatment of starved or diabetic rats results in the rapid decline in the hepatic concentration of mHMG-CoA synthase mRNA and protein [72,73]. In addition, the enzyme reverts to the succinylated (inhibited) state during refeeding of starved rats [74].…”
Section: Enzymes Involved In the Partitioning Of Fatty Acids Between mentioning
confidence: 99%